2011
DOI: 10.1002/jctb.2716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of struvite seed crystal on MAP crystallization

Abstract: BACKGROUND: There has been considerable controversy over the effect of seed crystal additions on crystallization of magnesium ammonium phosphate hexahydrates (MAP). In this study, batch experiments were carried out to verify this effect using synthetic solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 31 publications
1
14
0
4
Order By: Relevance
“…It was found that the addition of appropriate seed crystals could increase the rate of crystallization and reduce the induction time and equilibration time significantly. 33 Our former research showed that fluorapatite/calcite mixed seed crystals can induced the removal of fluoride. 18 The mixed seed crystals of fluorapatite/calcite can only induce the formation of Ca 5 (PO 4 ) 3 F and not the formation of other solids in Table 4.…”
Section: Effect Of Coexisting Ions Effect Of Coexisting Cationsmentioning
confidence: 99%
“…It was found that the addition of appropriate seed crystals could increase the rate of crystallization and reduce the induction time and equilibration time significantly. 33 Our former research showed that fluorapatite/calcite mixed seed crystals can induced the removal of fluoride. 18 The mixed seed crystals of fluorapatite/calcite can only induce the formation of Ca 5 (PO 4 ) 3 F and not the formation of other solids in Table 4.…”
Section: Effect Of Coexisting Ions Effect Of Coexisting Cationsmentioning
confidence: 99%
“…Seed crystals can significantly reduce the induction and equilibration times, especially for solutions with a lower supersaturation ratio [25]. In the present work, recycling the synthesized struvite to the reactor and injecting zeolite as an external material were applied to act as a seed substrate for struvite crystallization in the digester effluent and the concentrated seawater.…”
Section: Effect Of Seed Materialsmentioning
confidence: 99%
“…The problem of lower yield in struvite precipitation, in comparison with alkaline conditions, may be minimized using a continuous crystallizer operating at conditions of constant supersaturation . It has also been reported that using MAP seed crystals increased the efficiency of the crystal crop even at low supersaturations …”
Section: Introductionmentioning
confidence: 99%